Chiral pesticides as tracers of air-surface exchange - Bidleman, T. F.; Jantunen, L. M.; Harner, T.; Wiberg, K.; Wideman, J. L.; Brice, K.; Su, K.; Falconer, R. L.; Aigner, E. J.; Leone, A. D.; Ridal, J. J.; Kerman, B.; et al. (Environmental Pollution, 1998)
The enantiomers of chiral pesticides are selectively broken down in soil and water to yield residues and metabolites, which are non-racemic. The distinctive enantiomer signatures of residues are preserved upon volatilization, providing site-specific tracers for air-soil and air-water exchange. Applications of enantiomeric tracers include distinguishing the atmospheric transport of freshly applied pesticides from those which are 'recycled' from lakes, oceans and soil, and investigating biotic vs abiotic degradation pathways. Examples are given of using pesticide enantiomers to follow volatilization from the Great Lakes and arctic waters and as indicators of pesticide emissions from agricultural soils. Copyright (C) 1998 Elsevier Science Ltd